The Phenomenon of English Usage in Indonesian Cyberspace - Aditya, Rangga; Aminah, Sitti; Harmilawati, Harmilawati; Sabaruddin, Sabaruddin (JLE: Journal of Literate of English Education Study Program, 2025)
This study explores the growing trend of English language usage in Indonesian cyberspaces, particularly in social media comments. The researchers employ a qualitative research approach, specifically a phenomenological study. Data is collected using the documentation method, through screenshots of comments containing English on social media platforms such as Instagram, YouTube, TikTok, and Facebook. This methodology allows for an in-depth examination of the real-world manifestations of English usage in Indonesian digital communication. This research aims to understand the motivations, contexts, and implications of this linguistic phenomenon. The results show that the use of English in Indonesian online spaces shows how language, technology, culture, and worldwide connections mix together. It shows Indonesia is more involved in global online talks while trying to keep its own language and culture. The findings suggest that English usage in Indonesian cyberspace is a complex phenomenon driven by various factors, including globalization, digital connectivity, and changing perceptions of language prestige.